The Challenge of Domestic Intelligence in a Free Society A Multidisciplinary Look at the Creation of a U.S. Domestic Counterterrorism Intelligence Agency - Jackson, Brian A. (RAND Corporation, 2009)
Whether U.S. terrorism-prevention efforts match the threat continues to be central in policy debate. Part of this debate is whether the United States needs a dedicated domestic counterterrorism intelligence agency. This book examines such an agency's possible capability, comparing its potential effectiveness with that of current efforts, and its acceptability to the public, as well as various balances and trade-offs involved.